Microwave-Processable Cu Nanostructures -the Morphology and Chemical Properties - Nurul Akmal, Che Lah; Murthy, Puhanes (Elsevier Ltd., 2024)
The work presented a facile method using a domestic microwave-assisted technique in synthesising the Cu nanostructures solution. By controlling the microwave reaction time, the morphological structures and the ultra- fast growth of the as-synthesised Cu nanostructures are varied. The method is much preferable as compared to the conventional hydrothermal method due to the ultrafast supersaturation of Cu nuclei and high-quality structures. Those different morphologies with different average size distributions show a direct influence on their intrinsic physical behaviour. The study focuses on the morphology, particle size distribution and element bonding effect of the growth reaction and solution’s concentration. The combination of the CuSO4⋅5H2O, PEG (polyethylene glycol) and PVP (polyvinyl pyrrolidone) without any extra reagents shows the capabilities of mixture to yield the Cu nanostructures with the average particle size distribution below 100 nm. The produced Cu nanostructures via microwave-assisted demonstrated that the allocated time of reaction (~7 mins) shows a good supersaturated homogeneous nucleated suspension yield. Simultaneously, they undergo a size-dependent multi-stage aggregation mechanism to yield different morphologies of Cu nanostructures.